IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN TERPADU (KTP-el) DI KABUPATEN SUKABUMI - Dian Purwanti (Jurnal Administrasi Publik, 2017)
Implementation of Integrated Population Policy Administration Service (KTP-el). The increasing number of population in the regency of sukabumi encouraged to do a good recording of demographic data for population data is needed in the planning and evaluation of development. analyze the implementation of population policy in an integrated administrative services in providing services to people in the Department of Population and Civil Registration Sukabumi and analyzing the factors supporting and restricting. Type of this research is a descriptive qualitative approach. Administration policy on population intergrated in this study focused on basic services ID CARD which includes: basic policies or regulations adopted, procedure of making ID CARD services, document administration, as well as supporting and restricting factors of policy implementation. The results showed that the policy of centralization management card residents is Poor City Government step forward, especially in the field of public service to spruce up the residency to the administrative system in one centralized place to facilitate Government of sukabumi in accessing and mapping society so that in making policies that others have valid data.